Level of Sex Hormone Binding Globulin (SHBG) in Sera of Iraqi Women with Polycystic Ovary Syndrome Correlating Infertility - A.Sharhan, Zahraa; A. Ibrahim, Suhad; S. Al_Taie, Zahraa; Abdo Ahmed, Waled; M. Yusop, Rahimi (Al-Nahrain Journal of Science, 2025)
Ovulatory abnormalities are a prevalent cause of infertility in women, and they can result in PCOS, or polycystic ovary syndrome. This study aimed to evaluate and compare fasting blood sugar (FBS), insulin, insulin resistance (IR-OMO), sex hormone binding globulin (SHBG), and follicular, in addition to vitamin D3, stimulating hormone (FSH), testosterone (TT), estrogen (E2), luteinizing hormone (LH), prolactin (PRL), and the incidence of PCOS, associated with primary infertility in sera samples of Iraqi women. A total of 70 primary infertility women, and 30 apparently healthy controls were included in this study, their ages were ranged between 19 - 40 years. Blood samples were collected from patient in addition of healthy controls as (C group). The levels of FSH, LH, prolactin, TT, E2, IR-HOMO, and FBS were higher significantly (p˂0.001) in patient groups than C group. Results showed that serum levels of SHBG in patient (3.014±0.26 ng/ml) were decreased significantly in comparison with its levels (9.975 ±0.72 ng/ml) in sera sample of C group. On the other hand, vit. D3 levels of patients (11.78 ±1.41ng/ml) were also significantly decreased in comparison with C group (18.13 ±4.07ng/ml). Furthermore, it was found that there was non-significant positive correlation between serum levels of SHBG and LH, TT, E2, insulin, IR-HOMO, VITD3, and negatively associated with FSH, PRL and FSB in patients. Thus, it can be stated that the decreases of level SHBG were associated PCOS with primary infertility.